2011
DOI: 10.1111/j.1600-0609.2011.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, physical function and MRI T2* in elderly low-risk MDS patients treated to a haemoglobin level of ≥120 g/L with darbepoetin alfa ± filgrastim or erythrocyte transfusions

Abstract: In elderly anaemic MDS patients, an increment in haemoglobin is associated with improved QoL, whether induced by growth factor treatment or transfusion therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 35 publications
1
52
1
Order By: Relevance
“…Reported practices in this survey are consistent with a restrictive transfusion strategy, contrary to results of a single‐arm MDS study indicating improved quality of life, physical and cognitive function at higher haemoglobin levels . Given the paucity of prospective evidence to guide practice in MDS, haematologists may be extrapolating from trials conducted in acute contexts, such as intensive care and gastrointestinal tract bleeding, which support restrictive strategies .…”
Section: Discussionmentioning
confidence: 99%
“…Reported practices in this survey are consistent with a restrictive transfusion strategy, contrary to results of a single‐arm MDS study indicating improved quality of life, physical and cognitive function at higher haemoglobin levels . Given the paucity of prospective evidence to guide practice in MDS, haematologists may be extrapolating from trials conducted in acute contexts, such as intensive care and gastrointestinal tract bleeding, which support restrictive strategies .…”
Section: Discussionmentioning
confidence: 99%
“…A more intensive initial transfusion regimen aiming at a higher Hb level does not necessarily mean a higher transfusion rate, once the target Hb is reached (Nilsson-Ehle et al, 2011). Still, to receive repeated blood transfusions is not without risks: patients can for example, develop acute and delayed transfusion reaction and iron overload (Hellstrom-Lindberg, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on the use of darbepoetin +/-G-CSF and transfusions to reach a target Hb level of 120 g/L showed that EORTC QLQ-C30 QoL scores improved significantly during the study, with similar results for transfused and untransfused patients, though the impact of transfusions on daily life was not evaluated [23].…”
Section: Discussionmentioning
confidence: 97%